Synonymous codon usage bias in plant mitochondrial genes is associated with intron number and mirrors species evolution. - Wenjing Xu; Tian Xing; Mingming Zhao; Xunhao Yin; Guangmin Xia; Mengcheng Wang (PLoS ONE, 2015)
Synonymous codon usage bias (SCUB) is a common event that a non-uniform usage of codons often occurs in nearly all organisms. We previously found that SCUB is correlated with both intron number and exon position in the plant nuclear genome but not in the plastid genome; SCUB in both nuclear and plastid genome can mirror the evolutionary specialization. However, how about the rules in the mitochondrial genome has not been addressed. Here, we present an analysis of SCUB in the mitochondrial genome, based on 24 plant species ranging from algae to land plants. The frequencies of NNA and NNT (A- and T-ending codons) are higher than those of NNG and NNC, with the strongest preference in bryophytes and the weakest in land plants, suggesting an association between SCUB and plant evolution. The preference for NNA and NNT is more evident in genes harboring a greater number of introns in land plants, but the bias to NNA and NNT exhibits even among exons. The pattern of SCUB in the mitochondrial genome differs in some respects to that present in both the nuclear and plastid genomes.